The TAL Effector AvrBs3 from Xanthomonas campestris pv. vesicatoria Contains Multiple Export Signals and Can Enter Plant Cells in the Absence of the Type III Secretion Translocon - Scheibner, Felix; Marillonnet, Sylvestre; Büttner, Daniela (Frontiers in Microbiology, 2017)
Pathogenicity of the Gram-negative plant-pathogenic bacterium Xanthomonas campestris pv. vesicatoria depends on a type III secretion (T3S) system which translocates effector proteins into plant cells. Effector protein delivery is controlled by the T3S chaperone HpaB, which presumably escorts effector proteins to the secretion apparatus. One intensively studied effector is the transcription activator-like (TAL) effector AvrBs3, which binds to promoter sequences of plant target genes and activates plant gene expression. It was previously reported that type III-dependent delivery of AvrBs3 depends on the N-terminal protein region. The signals that control T3S and translocation of AvrBs3, however, have not yet been characterized. In the present study, we show that T3S and translocation of AvrBs3 depend on the N-terminal 10 and 50 amino acids, respectively. Furthermore, we provide experimental evidence that additional signals in the N-terminal 30 amino acids and the region between amino acids 64 and 152 promote translocation of AvrBs3 in the absence of HpaB. Unexpectedly, in vivo translocation assays revealed that AvrBs3 is delivered into plant cells even in the absence of HrpF, which is the predicted channel-forming component of the T3S translocon in the plant plasma membrane. The presence of HpaB- and HrpF-independent transport routes suggests that the delivery of AvrBs3 is initiated during early stages of the infection process, presumably before the activation of HpaB or the insertion of the translocon into the plant plasma membrane.